(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Cotton stalk biomass was treated with NaOH and NaOH-steam pretreatements to get maximum cellulose content. Three factors with three levels such as biomass concentration (5, 10 and 15%), NaOH concentration (1, 3 and 5%) and residence time (4, 6 and 8 h) was performed through Box-Bhenken Design of response surface methodology. The treatment was performed with and without heating at 121oC for 15min and 15psi in an autoclave. Among these two types of treatment, maximum yield of cellulose content 87.80% was observed with 5% w/v NaOH concentration, 10g substrate loading and 4h residence time. The substrate having high cellulose content under optimized pretreatment conditions were analysed through FTIR revealing efficiency of pretreatment. The proposed model for this study was found significant in terms of lower p<0.05 values and findings of this study could be utilized for further processes like saccharification and fermentation to bioethanol. Bangladesh J. Sci. Ind. Res.54(1), 73-82, 2019